Social Participation, Cognitive Health, and Mental Health in Thai Older Adults: Insights from the HART National Panel During the covid-19 Pandemic. - Chen, I-Chun; Phanumartwiwath, Anuchit (Journal of Gerontological Social Work, 2026)
This cross-sectional study examined associations between mental health, social participation, and cognitive function among 3,607 Thai older adults using data from Wave 4 of the Health, Aging, and Retirement in Thailand (HART) project, collected in 2020 during the COVID-19 pandemic. Controlling for demographics, hierarchical regression revealed higher depressive symptoms (CES-D-10) linked to lower cognitive performance. Formal social participation showed a modest buffering effect (β = 0.008, p =.002), despite an adverse main effect (β = -0.012, p <.001), likely from pandemic-related restrictions. Social networks had a positive partial correlation (r = 0.082, p <.001). Results advocate community-based interventions, including virtual formats, to support cognitive resilience.